2021
DOI: 10.2166/wcc.2021.282
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced index for water body delineation and area calculation using Google Earth Engine: a case study of the Manchar Lake

Abstract: The sustainability of the hydrological and ecological ecosystems of any region requires continuous monitoring of the water bodies. Recent advancements in satellite-based remote optical sensors, big data analysis and cloud computing have given new dimensions to the field of water body studies including their detection as well as analysis. The present study extends the existing methods to assess the contemporary surface water detection and monitoring techniques via remote sensing. The proposed technique implies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…• WIBI = NDWI -NDBI, where NDBI = (SWIR1 -NIR) / (SWIR1 + NIR) (Ismail et al 2022) Fourth, we used single-band reflectance information to improve the classification of water and snow or ice. After examining the validation results in the Ny-Ålesund study area, we identified a need to improve this distinction.…”
Section: Proposed Proceduresmentioning
confidence: 99%
“…• WIBI = NDWI -NDBI, where NDBI = (SWIR1 -NIR) / (SWIR1 + NIR) (Ismail et al 2022) Fourth, we used single-band reflectance information to improve the classification of water and snow or ice. After examining the validation results in the Ny-Ålesund study area, we identified a need to improve this distinction.…”
Section: Proposed Proceduresmentioning
confidence: 99%
“…By using GEE, it is possible to view and analyze all covers and uses of the earth with high spatial details in two and three dimensions. Many studies in different fields, such as vegetation monitoring [50], land use/cover maps [51] and their characteristics, such as the temperature of the earth's surface [52], monitoring of protected areas [53], monitoring of water resources and water bodies [54], agricultural products [55], and other types of remote sensing studies, have been carried out using this system.…”
Section: Google Earth Enginementioning
confidence: 99%
“…Recent advancement in satellite based‐remote sensing information with different spatial, spectral, radiometric, and temporal resolutions has given new dimensions to the water bodies studies (Ismail et al., 2021). Following the increase in the availability of satellite images, and image processing techniques, numerous research studies have attempted to extract and delineate water bodies from these images (Ouma & Tateishi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In testing, we employed images from the Moderate Resolution Imaging Spectroradiometer satellite, providing less detailed images, and the Land Remote-Sensing Satellite, offering highly detailed imagery. In essence, this study enhances water resource management by effectively combining data from multiple sources, even in adverse conditions, potentially advancing environmental protection and management efforts.Recent advancement in satellite based-remote sensing information with different spatial, spectral, radiometric, and temporal resolutions has given new dimensions to the water bodies studies (Ismail et al, 2021). Following the…”
mentioning
confidence: 99%
See 1 more Smart Citation